Access and Retrieval of Recent Journal Articles: A Comparative Study of Chemists and Geoscientists - Julie Hallmark (Issues in Science and Technology Librarianship)
This study describes the methods of access and retrieval of recent journal articles cited by geoscientists and chemists who work in academia, government, and industry. Citations, originally published during 2002, were selected from the references in current articles in 20 journal titles in the geosciences and 14 in chemistry. Each author received a personalized letter and brief questionnaire that addressed the methods of access and retrieval of one of those citations. Not surprisingly, a majority of respondents in both disciplines reported using the Internet for both access and retrieval, and many added insightful, substantive remarks that added depth and detail to the data analysis. The return rates of 75% in geoscience and 57% in chemistry suggest a high level of concern among these scientists for their journal literature. A comparison of the present results with similar unpublished data from a 1998 study illustrates the rapid evolution and acceptance of electronic journals; five years ago a majority of scientists in both disciplines used traditional (non-electronic) methods for access and retrieval of recent citations. Analysis of the information-seeking behavior of chemists and geologists as represented by citation patterns offers a unique view of the scientific endeavor.